Modified cu-ti alloy and method for producing the same

CN121294936BActive Publication Date: 2026-10-09CHINALCO RES INST OF SCI & TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511414619.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-10-09
Estimated Expiration
2045-09-29

AI Technical Summary

Technical Problem

[0006]本发明的主要目的在于提供一种改性Cu-Ti合金及其制备方法,以解决现有技术中存在Cu-Ti合金材料难以同时兼顾优良的强度与导电率的问题

Benefits of technology

[0017]By applying the technical solution of this invention, the modified Cu-Ti alloy in this application optimizes the distribution of multi-scale precipitated phases without affecting the basic properties of the alloy. These precipitated phases include microstructures with sizes ranging from 3 to 11 nm and 12 to 22 nm, respectively. They work together on the alloy matrix, resulting in significantly improved strength, plasticity, and electrical conductivity of the modified Cu-Ti alloy material. This is because the multi-scale precipitated phases not only increase the alloy's ability to coordinate deformation and allow for multiple deformation heat treatments, but also further induce the precipitation of more multi-scale precipitated phases. Furthermore, when the multi-scale precipitated phases and dislocations exhibit suitable coupling distribution characteristics, they can synergistically improve the alloy's strength, electrical conductivity, and plasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121294936B_ABST
    Figure CN121294936B_ABST
Patent Text Reader

Abstract

The application provides a modified Cu-Ti alloy and a preparation method thereof. The modified Cu-Ti alloy comprises 3.0-3.5 wt% of Ti elements, ≤0.02 wt% of B elements, ≤0.02 wt% of Zr elements and the balance of Cu elements in terms of mass percentage; wherein the modified Cu-Ti alloy comprises β'-Cu4Ti precipitated phases with a size of 3-11 nm and β'-Cu4Ti precipitated phases with a size of 12-22 nm. The above multi-scale precipitated phases can not only increase the coordinated deformation capacity of the alloy, but also can be adjusted and controlled by multiple deformation heat treatments, and can further induce more multi-scale precipitated phases to precipitate. Meanwhile, when the multi-scale precipitated phases and dislocations have a suitable coupling distribution characteristic, the strength, conductivity and plasticity of the alloy can be synergistically improved, so that the problem that the Cu-Ti alloy material is difficult to simultaneously consider excellent strength and conductivity is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of modified Cu-Ti alloy preparation technology, and more specifically, to a modified Cu-Ti alloy and its preparation method. Background Technology

[0002] Copper alloys are widely used in conductive materials due to their excellent electrical and thermal conductivity, strength, and elastic modulus. Among them, Cu-Be alloys are renowned for their superior electrical conductivity and mechanical properties. After appropriate solution treatment and aging, they can achieve very high strength and hardness, as well as excellent corrosion resistance and cold workability, making them the top copper alloy. However, their production costs are high, the process is relatively complex, their performance is highly sensitive to heat treatment, they have poor resistance to high-temperature stress relaxation, and their alloy properties are unstable, making them unsuitable for prolonged operation at high temperatures. Furthermore, beryllium and its compounds are toxic, posing a threat to human health and the environment; these shortcomings severely limit the further widespread application of this alloy. In addition, with the advancement of modern science and technology, electrical and electronic components are increasingly moving towards miniaturization, high density, and high integration, placing higher demands on the comprehensive performance of elastic elements. Simultaneously, with increasing awareness of environmental protection and conservation, non-toxic, pollution-free, low-energy-consumption, green, and recyclable materials have become the main development directions for elastic copper alloys. To address the shortcomings of traditional materials, people have sought and developed a series of new be-free elastic copper alloy materials, such as Cu-Ni-Si alloy, Cu-Ni-Sn alloy, and Cu-Ti alloy.

[0003] Cu-Ti alloys, similar to Cu-Be alloys, are both age-hardening elastic copper alloys with excellent properties such as corrosion resistance, wear resistance, and high-temperature stress relaxation resistance, comparable to Cu-Be alloys. They are promising key materials for replacing beryllium bronze. However, a key problem with this series of alloys is that while achieving high strength, their electrical conductivity is generally difficult to improve simultaneously. Whether produced by leading international Japanese companies or domestically produced Cu-Ti alloy sheets and strips by various Chinese companies, when the tensile strength reaches over 1000 MPa, the corresponding electrical conductivity is generally below 15% IACS. The key reason why the alloy conductivity is difficult to effectively improve is that even trace amounts of Ti dissolved in the alloy matrix lead to a significant decrease in the conductivity of Cu-Ti alloys. Therefore, how to effectively improve the conductivity of this series of alloys without compromising strength is an urgent problem to be solved.

[0004] Numerous studies, both domestically and internationally, have explored ways to effectively enhance the electrical conductivity of high-strength Cu-Ti alloys. For instance, aging in a H2 atmosphere promotes Ti precipitation within the Cu-Ti alloy matrix, leading to the formation of Cu4Ti and δ-TiH2 phases. This improves both conductivity and elongation, but reduces overall strength. Additionally, studies have investigated the effect of introducing ultra-low temperature cold rolling deformation before aging of Cu-1.5wt%Ti alloys on precipitation behavior. These studies found that after 90% deformation followed by aging, the hardness, yield strength, and tensile strength of Cu-1.5wt%Ti alloys with lower Ti content all showed some improvement. Furthermore, to better induce effective Ti precipitation from the alloy matrix, studies have also explored adding tertiary elements to improve conductivity, such as Fe, Ni, Sn, Zr, Co, Cr, Cd, B, and Mg. While these additions do have some influence on precipitation, the effect is not significant and remains insufficient to effectively address the common key issue of synergistic improvement in the strength and electrical properties of this alloy system. For example, after peak aging treatment, the Cu-4.5Ti-0.5Co alloy achieved hardness, yield strength, and tensile strength of 320 HV, 610 MPa, and 710 MPa, respectively, but its conductivity only increased to 8% IACS. While the addition of other tertiary components also had some impact on the alloy's conductivity, the overall effect on the increase in conductivity was not significant. Based on the control of tertiary components, there has been considerable research on further deformation heat treatment to improve the alloy's strength and conductivity, ultimately hoping to achieve a significant increase in both through the synergistic effect of deformation strengthening and precipitation strengthening. However, to date, most research on deformation heat treatment processes focuses more on directly cold rolling (room temperature cold rolling or ultra-low temperature cold rolling) the solution-quenched alloy, followed by isothermal aging, or on this basis, secondary cold rolling deformation + isothermal aging control. This not only results in poor coupling distribution of precipitated phases and dislocations, but also makes it difficult to effectively improve the conductivity when the alloy strength reaches above 1000 MPa. Furthermore, when the tensile strength of Cu-Ti alloy exceeds 1000 MPa, its elongation is generally low, sometimes even only about 1%, resulting in insufficient bending performance and easy cracking of high-strength Cu-Ti alloy strips. Especially for ultra-thin, irregularly shaped components using 0.1 mm thick Cu-Ti alloy strips, higher requirements are placed on the elongation of the alloy to meet its bending performance. Therefore, while further improving conductivity, how to further improve the plasticity of this series of alloy plates and strips is also a key issue in recent times.

[0005] Based on the performance requirements of next-generation high-strength conductive copper alloy elastic components, and considering that the key factors affecting the improvement of alloy strength, conductivity, and other properties remain composition and processing, especially processing, it is necessary to break away from traditional microstructure design and control approaches to achieve a synergistic improvement in the overall performance of this alloy system. Only through the development of new microstructure design and control processes can a breakthrough in the synergistic improvement of the overall performance of this alloy system be achieved. Therefore, it is essential to develop a high-strength conductive Cu-Ti alloy material and its preparation technology that do not increase alloy production costs while possessing excellent comprehensive performance, thereby better meeting the urgent needs of high-tech fields for this type of material. Furthermore, this novel Cu-Ti alloy material and its preparation process will also provide important inspiration and impetus for the further development of other novel metallic materials. Summary of the Invention

[0006] The main objective of this invention is to provide a modified Cu-Ti alloy and its preparation method, so as to solve the problem that Cu-Ti alloy materials in the prior art are difficult to simultaneously achieve excellent strength and conductivity.

[0007] To achieve the above objectives, according to one aspect of the present invention, a modified Cu-Ti alloy is provided, comprising, by mass percentage: 3.0 to 3.5 wt% Ti, ≤0.02 wt% B, ≤0.02 wt% Zr, and the balance being Cu; wherein the modified Cu-Ti alloy comprises β'-Cu4Ti precipitates with a size of 3 to 11 nm and β'-Cu4Ti precipitates with a size of 12 to 22 nm.

[0008] Furthermore, the dislocation density of the modified Cu-Ti alloy is (5~7)×10⁻⁶. 14 ·m -2 .

[0009] Furthermore, the spacing between adjacent particles of the β'-Cu4Ti precipitate phase with a size of 3 to 11 nm is 6 to 9 nm; and / or the spacing between adjacent particles of the β'-Cu4Ti precipitate phase with a size of 12 to 22 nm is 10 to 16 nm.

[0010] According to another aspect of the present invention, a method for preparing the aforementioned modified Cu-Ti alloy is provided, the method comprising the following steps performed sequentially: batching, casting, homogenization heat treatment, hot rolling deformation, cold rolling deformation, solution quenching treatment, pre-aging treatment, first cold rolling, aging with heating, second cold rolling, first aging with cooling, third cold rolling, isothermal aging, and second aging with cooling.

[0011] Furthermore, the temperature of the above-mentioned pre-aging treatment is 300-450℃, the heating rate of the pre-aging treatment stage is 150-300℃ / h, and after the pre-aging treatment is completed, it is air-cooled to 25-30℃.

[0012] Furthermore, the temperature of the first cold rolling is 25-30℃, the total deformation is 40-60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-20%; and / or the temperature of the heating aging is increased from 350℃ to 500℃, the heating rate is 0.5-4.6℃ / min, and water quenching is performed when the temperature of the heating aging is 500℃.

[0013] Furthermore, the temperature of the second cold rolling is 25-30℃, the total deformation is 40-60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-20%; and / or the temperature of the first cooling aging is reduced from 500℃ to 350℃, the cooling rate is 1.0-1.4℃ / min, and air cooling is performed when the temperature of the first cooling aging is 350℃.

[0014] Furthermore, the temperature of the third cold rolling is 25-30°C, the total deformation is 35-55%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-15%.

[0015] Furthermore, the isothermal aging temperature is 400–420°C, and the heating rate is greater than 100°C / min during the process of raising the temperature to the isothermal aging temperature. After isothermal aging for 1–7 hours, the temperature is raised to the highest temperature of the second cooling aging at a rate greater than 100°C / min for the second cooling aging. The second cooling aging reduces the temperature from 500°C to 400°C at a cooling rate of 1.0–1.4°C / min. When the temperature of the second cooling aging is 400°C, air cooling is performed.

[0016] Furthermore, the homogenization heat treatment temperature is 750–850℃, the time is 0.5–4h, and the heating rate during the process of heating to the homogenization heat treatment temperature is 20–80℃ / min; and / or the total deformation of hot rolling deformation is 60–80%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 10–20%; and / or the temperature of cold rolling deformation is 25–30℃, and the total deformation is 40–55%; and / or the solution quenching treatment temperature is 800–900℃, and the time is 2–5h.

[0017] By applying the technical solution of this invention, the modified Cu-Ti alloy in this application optimizes the distribution of multi-scale precipitated phases without affecting the basic properties of the alloy. These precipitated phases include microstructures with sizes ranging from 3 to 11 nm and 12 to 22 nm, respectively. They work together on the alloy matrix, resulting in significantly improved strength, plasticity, and electrical conductivity of the modified Cu-Ti alloy material. This is because the multi-scale precipitated phases not only increase the alloy's ability to coordinate deformation and allow for multiple deformation heat treatments, but also further induce the precipitation of more multi-scale precipitated phases. Furthermore, when the multi-scale precipitated phases and dislocations exhibit suitable coupling distribution characteristics, they can synergistically improve the alloy's strength, electrical conductivity, and plasticity. Attached Figure Description

[0018] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0019] Figure 1 A process flow diagram for preparing the modified Cu-Ti alloy according to this application is shown;

[0020] Figure 2 The diagram shows the hardness change during the first cooling aging of the alloy in the second cold-rolled state according to Example 1 of this application;

[0021] Figure 3 The diagram shows the change in electrical conductivity of the alloy in the second cold-rolled state during the first cooling aging process according to Example 1 of this application;

[0022] Figure 4 The diagram shows the hardness change during the first cooling aging of the alloy in the second cold-rolled state according to Example 3 of this application;

[0023] Figure 5 The diagram shows the change in electrical conductivity of the alloy in the second cold-rolled state during the first cooling aging process according to Example 3 of this application;

[0024] Figure 6 The diagram shows the hardness change during the first cooling aging of the alloy in the second cold-rolled state according to Example 5 of this application;

[0025] Figure 7 The diagram shows the change in electrical conductivity of the alloy in the second cold-rolled state during the first cooling aging process according to Example 5 of this application;

[0026] Figure 8 The diagram shows the hardness variation of the alloys in the third cold-rolled state after isothermal aging and second cooling aging according to Examples 1, 3 and 5 of this application;

[0027] Figure 9 The diagram shows the hardness variation of the alloys in the third cold-rolled state after isothermal aging and a second cooling aging, according to Examples 2, 4 and 6 of this application. Detailed Implementation

[0028] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0029] As analyzed in the background section of this application, the existing technology has the problem that Cu-Ti alloy materials cannot simultaneously achieve excellent strength and conductivity. In order to solve the above problems, this application provides a modified Cu-Ti alloy and its preparation method.

[0030] In a typical embodiment of this application, a modified Cu-Ti alloy is provided, comprising, by mass percentage: 3.0 to 3.5 wt% Ti, ≤0.02 wt% B, ≤0.02 wt% Zr, with the balance being Cu; wherein the modified Cu-Ti alloy includes β'-Cu4Ti precipitates with a size of 3 to 11 nm and β'-Cu4Ti precipitates with a size of 12 to 22 nm.

[0031] The modified Cu-Ti alloy in this application optimizes the distribution of multi-scale precipitated phases without affecting the alloy's fundamental properties. These precipitated phases include microstructures with sizes ranging from 3 to 11 nm and 12 to 22 nm, respectively. They work together on the alloy matrix, resulting in significantly improved strength, plasticity, and electrical conductivity in the modified Cu-Ti alloy. This is because the multi-scale precipitated phases not only increase the alloy's ability to coordinate deformation and allow for controlled deformation through multiple heat treatments, but also further induce the precipitation of more multi-scale precipitated phases. Furthermore, when the multi-scale precipitated phases and dislocations exhibit suitable coupling distribution characteristics, they can synergistically enhance the alloy's strength, electrical conductivity, and plasticity.

[0032] In one embodiment of this application, the dislocation density of the modified Cu-Ti alloy is (5~7)×10⁻⁶. 14 ·m -2 .

[0033] Smaller precipitate phases help pin dislocations more effectively, preventing them from slipping and annihilating, while larger precipitate phases help reduce electron scattering and improve electrical conductivity. The preferred dislocation density helps balance the overall properties of the modified Cu-Ti alloy.

[0034] In one embodiment of this application, the spacing between adjacent particles of the β'-Cu4Ti precipitate phase with a size of 3 to 11 nm is 6 to 9 nm; and / or the spacing between adjacent particles of the β'-Cu4Ti precipitate phase with a size of 12 to 22 nm is 10 to 16 nm.

[0035] By setting the spacing between adjacent particles of the β'-Cu4Ti precipitate phase with sizes of 3–11 nm and 12–22 nm within the above ranges, the aggregation of coarse precipitate phases was effectively suppressed, avoiding the potential performance degradation. At the same time, the uniformity and stability of the internal structure of the alloy were ensured, further improving the performance of the alloy.

[0036] In another typical embodiment of this application, a method for preparing the above-mentioned modified Cu-Ti alloy is provided, such as... Figure 1 As shown, the preparation method includes the following steps performed in sequence: batching, casting, homogenization heat treatment, hot rolling deformation, cold rolling deformation, solution quenching treatment, pre-aging treatment, first cold rolling, aging with heating, second cold rolling, first cooling aging, third cold rolling, isothermal aging, and second cooling aging.

[0037] This invention considers that most alloys not only precipitate phases during continuous heating, but also, depending on the alloy composition, precipitate phases of various types and scales. Therefore, if pre-aging at a higher temperature is introduced after solution treatment, multi-scale precipitate phases can definitely precipitate within the alloy matrix, provided the temperature range and heating rate are appropriate. Once formed, multi-scale precipitate phases not only increase the alloy's ability to coordinate deformation and allow for multiple deformation heat treatments, but also further induce the precipitation of more multi-scale precipitate phases. Furthermore, when multi-scale precipitate phases exhibit suitable coupling distribution characteristics with dislocations, they can synergistically improve the alloy's strength, conductivity, and plasticity. Therefore, this invention breaks away from the traditional deformation heat treatment process routes for controlling the microstructure and properties of Cu-Ti alloys, such as solution quenching → cold deformation → isothermal aging, or solution quenching → cold deformation → isothermal aging → cold deformation → isothermal aging. Instead, it innovatively proposes and develops the following novel control process route: solution quenching → pre-aging with increased temperature → first cold rolling deformation → aging with increased temperature → second cold rolling deformation → first aging with decreased temperature → third cold rolling deformation → isothermal aging + second aging with decreased temperature. This process route first controls the pre-aging of the solution-quenched alloy with increased temperature, which promotes the rapid precipitation of a large number of multi-scale precipitates within the alloy matrix. This not only synergistically influences the degree of dislocation slip, pile-up, and annihilation during subsequent cold rolling, but also actively affects the diffusion and enrichment of solute elements, as well as the growth and distribution of precipitates during aging. Consequently, the alloy's strength, plasticity, and conductivity are effectively improved. Furthermore, building upon the initial introduction of pre-aging temperature control, this invention breaks away from traditional deformation heat treatment control methods (cold rolling + isothermal aging process). It innovatively proposes a novel approach to synergistically control the precipitation, growth, and coupling distribution of multi-scale precipitate phases with dislocations through a multi-process, multi-level non-isothermal heat treatment involving one cold rolling deformation + pre-aging temperature control, a second cold rolling + first cooling temperature control, and a third cold rolling + isothermal aging + second cooling temperature control. This method not only allows for the reasonable coarsening of the multi-scale precipitate phases regulated by pre-aging temperature control, but also induces the precipitation of more multi-scale precipitate phases and influences dislocation slip, pile-up, annihilation, and distribution. Ultimately, based on the formation of multi-scale precipitate phases and their coupling distribution with dislocations, the strength, conductivity, and plasticity of this alloy system can be significantly improved.

[0038] In one embodiment of this application, the temperature of the pre-aging treatment is 300-450°C, the heating rate of the pre-aging treatment stage is 150-300°C / h, and the temperature is air-cooled to 25-30°C after the pre-aging treatment is completed.

[0039] This application utilizes carefully designed temperature, heating rate, and time parameters for pre-aging treatment to facilitate the control of multi-scale precipitated phases within the alloy matrix.

[0040] In one embodiment of this application, the temperature of the first cold rolling is 25-30°C, the total deformation is 40-60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-20%; and / or the temperature of the heating and aging process is increased from 350°C to 500°C, the heating rate is 0.5-4.6°C / min, and water quenching is performed when the temperature of the heating and aging process is 500°C.

[0041] This application specifies in detail the specific conditions for the first cold rolling and the heating aging. By combining cold rolling with heating aging, not only can the multi-scale precipitate phase regulated by the heating pre-aging be reasonably coarsened, but it can also induce more multi-scale precipitate phases to precipitate and affect dislocation slip, pile-up, annihilation and distribution.

[0042] In one embodiment of this application, the temperature of the second cold rolling is 25-30°C, the total deformation is 40-60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-20%; and / or the temperature of the first cooling aging is reduced from 500°C to 350°C, the cooling rate is 1.0-1.4°C / min, and air cooling is performed when the temperature of the first cooling aging is 350°C.

[0043] This application specifies in detail the conditions for the second cold rolling and the first cooling aging. This method, combining cold rolling and cooling aging, not only effectively utilizes the residual thermal stress within the alloy to promote dislocation rearrangement and optimize the distribution of precipitated phases, but also prevents performance degradation caused by excessive heat treatment. During the first cooling aging process, as the temperature decreases, dislocation activity decreases, and the growth rate of the precipitated phase is controlled, thus forming a unique microstructure within the alloy—a multi-scale coupled distribution of precipitated phases and dislocations. This provides an ideal strengthening mechanism for the alloy while maintaining good plasticity and electrical conductivity.

[0044] In one embodiment of this application, the temperature of the third cold rolling is 25-30°C, the total deformation is 35-55%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5-15%.

[0045] By controlling the specific conditions of the third cold rolling within the aforementioned range, the microstructure of the alloy was further refined, resulting in a more uniform size distribution of the previously formed precipitated phases. This also increased the alloy's deformation energy storage, providing greater flexibility for subsequent heat treatment. Through this step, the alloy not only withstands more processing deformation but also exhibits better performance stability during subsequent heat treatment.

[0046] In one embodiment of this application, the isothermal aging temperature is 400-420°C, and the heating rate during the process of raising the temperature to the isothermal aging temperature is greater than 100°C / min. After isothermal aging for 1-7 hours, the temperature is raised to the highest temperature of the second cooling aging at a rate greater than 100°C / min for the second cooling aging. The second cooling aging reduces the temperature from 500°C to 400°C at a cooling rate of 1.0-1.4°C / min. When the temperature of the second cooling aging is 400°C, air cooling is performed.

[0047] This application employs a combined isothermal aging and secondary cooling aging method, which further optimizes the microstructure of the alloy. First, by controlling the isothermal aging temperature and time within the aforementioned range, the growth of fine precipitate phases is promoted, while dislocation density is reduced, achieving a purifying effect on the matrix. Then, during the secondary cooling aging process, the continuous cooling from high to low temperature not only mitigates the adverse risks associated with sudden temperature changes but also promotes the growth of larger-scale precipitate phases, further enhancing the alloy's strength and toughness.

[0048] In one embodiment of this application, the homogenization heat treatment temperature is 750–850°C, the time is 0.5–4 h, and the heating rate during the process of heating to the homogenization heat treatment temperature is 20–80°C / min; and / or the total deformation of hot rolling deformation is 60–80%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 10–20%; and / or the temperature of cold rolling deformation is 25–30°C, and the total deformation is 40–55%; and / or the solution quenching treatment temperature is 800–900°C, and the time is 2–5 h.

[0049] By controlling the conditions of homogenization heat treatment, hot rolling deformation, cold rolling deformation, and subsequent solution quenching within the aforementioned ranges, these pretreatment steps aim to minimize compositional segregation and microstructural defects in the alloy ingot, laying a solid foundation for subsequent pre-aging and deformation heat treatments. The combination of homogenization heat treatment and hot rolling deformation optimizes the original microstructure of the alloy through high-temperature dissolution and dynamic recrystallization, reducing initial dislocation density and thus improving the overall homogeneity of the alloy and the effectiveness of subsequent heat treatments. Solution quenching, through rapid cooling, retains a large number of supersaturated solute atoms, providing the necessary preconditions for pre-aging treatment and ensuring optimized formation and distribution of subsequent precipitated phases.

[0050] The beneficial effects of this application will be further illustrated below with reference to the embodiments.

[0051] The following examples are based on Figure 1 The modified Cu-Ti alloy preparation process is shown in the flowchart below.

[0052] Example 1

[0053] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum level is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1250℃. This temperature is held for 5 minutes, and then the melt is stirred electromagnetically for 70 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically as follows: homogenization heat treatment + hot rolling deformation. (Homogeneous heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → Cold rolling deformation (deformation temperature: room temperature, deformation: 50%) → Solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → Pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → First cold rolling + aging treatment (Deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 1.5℃ / min, water quenching treatment is performed directly after aging to the highest temperature) → Second cold rolling + cooling aging (Deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, cooling aging to the lowest temperature) The process involves several steps: First, the alloy is directly air-cooled after reaching the set temperature. Then, it undergoes a third cold rolling process (deformation temperature: room temperature, deformation amount: 45%, per pass deformation amount: 10%, deformation method: unidirectional synchronous rolling). Next, it undergoes isothermal aging followed by cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.2℃ / min, and then directly air-cooled after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys are characterized, as shown in Tables 1 and 2. Figure 2 As shown in 3 and 8.

[0054] Example 2

[0055] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum level is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1200℃. This temperature is held for 3 minutes, and then the melt is stirred electromagnetically for 30 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically: homogenization heat treatment + hot rolling deformation. (Homogeneous heat treatment temperature: 750℃, time: 0.5h; heating rate: 20℃ / min, hot rolling deformation after homogenization: 60%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → Cold rolling deformation (deformation temperature: room temperature, deformation: 40%) → Solution quenching treatment (temperature: 800℃, time: 2h, water quenching) → Pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 150℃ / h, air cooling to room temperature after pre-aging) → First cold rolling + heating First aging (deformation temperature: room temperature, deformation amount: 40%, deformation method: unidirectional synchronous rolling, deformation per pass: 5%, aging temperature range: 350→500℃, heating rate: 0.5℃ / min, water quenching treatment performed directly after aging to the highest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 60%, deformation method: unidirectional synchronous rolling, deformation per pass: 20%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, cooling aging to the lowest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 60%, deformation method: unidirectional synchronous rolling, deformation per pass: 20%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, water quenching treatment performed directly after ...40%, deformation method: unidirectional synchronous rolling, deformation per pass: 5%, heating aging temperature range: 350→500℃, heating rate: 0.5℃ / min, water quenching treatment performed directly after aging to the lowest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 60 The process involves several steps: First, air cooling is performed directly after the initial temperature change. Then, a third cold rolling process is initiated (deformation temperature: room temperature, deformation amount: 55%, per pass deformation amount: 15%, deformation method: unidirectional synchronous rolling). Next, isothermal aging is performed followed by cooling aging (isothermal temperature: 420℃, heating rate: 150℃ / min, time: 7h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.4℃ / min, followed by direct air cooling after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys are characterized, as shown in Tables 1 and 2. Figure 9 As shown.

[0056] Example 3

[0057] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum level is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1300℃. This temperature is held for 7 minutes, and then the melt is stirred electromagnetically for 90 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically as follows: homogenization heat treatment + hot rolling. Hot rolling deformation (homogenization heat treatment temperature: 850℃, time: 4h; heating rate: 80℃ / min, hot rolling deformation after homogenization: 80%, deformation per pass: 20%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation: 55%) → solution quenching treatment (temperature: 900℃, time: 5h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 240℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + heating First aging (deformation temperature: room temperature, deformation amount: 60%, deformation method: unidirectional synchronous rolling, deformation per pass: 20%, aging temperature range: 350→500℃, heating rate: 3.4℃ / min, water quenching treatment performed directly after aging to the highest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 40%, deformation method: unidirectional synchronous rolling, deformation per pass: 5%, cooling aging temperature range: 500→350℃, cooling rate: 1.0℃ / min, cooling aging to the lowest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 40%, deformation method: unidirectional synchronous rolling, deformation per pass: 5%, cooling aging temperature range: 500→350℃, cooling rate: 1.0℃ / min, cooling aging to the lowest temperature) The process involves several steps: First, the alloy is directly air-cooled after reaching the set temperature. Then, it undergoes a third cold rolling process (deformation temperature: room temperature, deformation amount: 35%, per pass deformation amount: 5%, deformation method: unidirectional synchronous rolling). Next, it undergoes isothermal aging followed by cooling aging (isothermal temperature: 400℃, heating rate: 150℃ / min, time: 1h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.0℃ / min, and air cooling after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys are characterized, as shown in Tables 1 and 2. Figure 2 As shown in 3 and 8.

[0058] Example 4

[0059] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum level is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1300℃. This temperature is held for 7 minutes, and then the melt is stirred electromagnetically for 60 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically as follows: homogenization heat treatment + hot rolling deformation. (Homogeneous heat treatment temperature: 850℃, time: 3h; heating rate: 75℃ / min, hot rolling deformation after homogenization: 60%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → Cold rolling deformation (deformation temperature: room temperature, deformation: 45%) → Solution quenching treatment (temperature: 900℃, time: 3.5h, water quenching) → Pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 200℃ / h, air cooling to room temperature after pre-aging) → First cold rolling + heating First aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 3.0℃ / min, water quenching treatment performed directly after aging to the highest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 55%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, cooling aging to the lowest temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 55%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, water quenching treatment performed directly after ... The process involves several steps: First, direct air cooling after temperature adjustment. Then, a third cold rolling process is performed (deformation temperature: room temperature, deformation amount: 45%, per pass deformation amount: 10%, deformation method: unidirectional synchronous rolling). Next, isothermal aging is followed by cooling aging (isothermal temperature: 420℃, heating rate: 150℃ / min, time: 7h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.4℃ / min, and air cooling after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys are characterized, as shown in Tables 1 and 2. Figure 9 As shown.

[0060] Example 5

[0061] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum degree is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1200℃. This temperature is held for 6 minutes, and then the melt is stirred electromagnetically for 30-90 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically as follows: homogenization heat treatment + heat... Hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 4h; heating rate: 60℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation: 45%) → solution quenching treatment (temperature: 850℃, time: 4h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 300℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + heating Aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 4.6℃ / min, water quenching treatment performed directly after aging to the maximum temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, water quenching treatment performed directly after aging to the maximum temperature) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, water quenching treatment performed directly after aging to the maximum temperature) The process involved several steps: First, air cooling after initial cooling at low temperatures. Then, a third cold rolling process was performed (deformation temperature: room temperature, deformation amount: 45%, per pass: 10%, deformation method: unidirectional synchronous rolling). Next, isothermal aging was followed by cooling aging (isothermal temperature: 420℃, heating rate: 150℃ / min, time: 4h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling temperature range: 500→400℃, cooling rate: 1.4℃ / min, followed by direct air cooling after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys were characterized, as shown in Tables 1 and 2. Figure 2 As shown in 3 and 8.

[0062] Example 6

[0063] First, the alloy is prepared according to the designed composition values ​​and then melted and cast. The raw materials used for melting and casting are 99.9 wt% electrolytic high-purity Cu, sponge Ti, and other intermediate alloys. First, a Cu-3.3 wt% Ti alloy is prepared and placed in a medium-frequency induction melting furnace. Once the vacuum level is less than 0.1 Pa, the temperature is raised directly using high-power heating until the melt is completely melted and the temperature reaches 1250℃. This temperature is held for 7 minutes, and then the melt is stirred electromagnetically for 90 seconds. After the melt temperature stabilizes at around 1250℃, casting begins, controlling the casting speed to minimize shrinkage cavities. Then, the ingot undergoes homogenization treatment and subsequent multi-process control, specifically as follows: homogenization heat treatment + hot rolling deformation. (Homogeneous heat treatment temperature: 850℃, time: 4h; heating rate: 80℃ / min, hot rolling deformation after homogenization: 60%, deformation per pass: 20%, deformation method: unidirectional synchronous rolling) → Cold rolling deformation (deformation temperature: room temperature, deformation: 50%) → Solution quenching treatment (temperature: 900℃, time: 4h, water quenching) → Pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 286℃ / h, air cooling to room temperature after pre-aging) → First cold rolling + aging treatment Deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, heating and aging temperature range: 350→500℃, heating rate: 3.5℃ / min, water quenching treatment is performed directly after heating and aging to the highest temperature) → second cold rolling + cooling and aging (deformation temperature: room temperature, deformation amount: 55%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling and aging temperature range: 500→350℃, cooling rate: 1.4℃ / min, cooling and aging to the lowest temperature) The process involves several steps: first, air cooling; second, third cold rolling (deformation temperature: room temperature, deformation amount: 45%, per pass deformation amount: 10%, deformation method: unidirectional synchronous rolling); third, isothermal aging + cooling aging (isothermal temperature: 400℃, heating rate: 150℃ / min, time: 4-7h, then directly heating at a rate of 150℃ / min to the highest cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.4℃ / min, and air cooling after cooling to the lowest temperature). Finally, the microhardness, electrical conductivity, and tensile properties of typical aged alloys are characterized, as shown in Tables 1 and 2. Figure 9 As shown.

[0064] Example 7

[0065] The difference from Example 1 is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 130℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 1.5℃ / min, aging to the highest temperature) The process involves several steps: (direct water quenching after initial cooling) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, air cooling after cooling to the minimum temperature) → third cold rolling (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → isothermal aging + cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the maximum cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.2℃ / min, air cooling after cooling to the minimum temperature). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0066] Example 8

[0067] The difference from Example 1 is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 5.0℃ / min, aging to the highest temperature) The process involves several steps: (direct water quenching after initial cooling) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, air cooling after cooling to the minimum temperature) → third cold rolling (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → isothermal aging + cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the maximum cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.2℃ / min, air cooling after cooling to the minimum temperature). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0068] Example 9

[0069] The difference from Example 1 is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, aging temperature range: 350→500℃, heating rate: 1.5℃ / min, aging to the highest temperature) The process involves several steps: (direct water quenching after initial cooling) → second cold rolling + cooling aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, air cooling after cooling to the minimum temperature) → third cold rolling (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → isothermal aging + cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the maximum cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 0.8℃ / min, air cooling after cooling to the minimum temperature). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0070] Comparative Example 1

[0071] The difference from Example 1 is that pre-aging with heating is not performed. The process is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → first cold rolling + heating aging (deformation temperature: room temperature, deformation: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, heating aging temperature range: 350→500℃, heating rate: 1.5℃ / min, water quenching treatment is performed directly after heating aging to the highest temperature) → second cold rolling + cooling The aging process involved three stages: First, a third cold rolling (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, followed by air cooling after reaching the minimum temperature) → second, third cold rolling (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → isothermal aging + cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the maximum cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.2℃ / min, followed by air cooling after reaching the minimum temperature). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0072] Comparative Example 2

[0073] The difference from Example 1 is that no heating aging is performed. The process is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → heating pre-aging treatment (heating pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → first cold rolling (deformation temperature: room temperature, deformation: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, direct water quenching) → second cold rolling + cooling The aging process involved three stages: warm aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, followed by direct air cooling after reaching the minimum temperature) → third cold rolling (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling) → isothermal aging + cooling aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, then directly heating at a rate of 150℃ / min to the maximum cooling aging temperature for cooling aging, cooling aging temperature range: 500→400℃, cooling rate: 1.2℃ / min, followed by direct air cooling after reaching the minimum temperature). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0074] Comparative Example 3

[0075] The difference from Example 1 is that a second cooling aging is not performed. The process is as follows: homogenization heat treatment + hot rolling deformation (homogenization heat treatment temperature: 800℃, time: 2h; heating rate: 50℃ / min, hot rolling deformation after homogenization: 70%, deformation per pass: 15%, deformation method: unidirectional synchronous rolling) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + aging (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 70%) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → solution quenching treatment (temperature: 850℃, time: 3h, water quenching) → pre-aging treatment (pre-aging temperature range: 300-450℃, heating rate: 180℃ / h, air cooling to room temperature after pre-aging) → first cold rolling + pre-aging treatment (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 70%) → cold rolling deformation (deformation temperature: room temperature, deformation amount: 50%) → hot rolling deformation (deformation per pass: 70%) → hot ... The typical aged alloy underwent a series of treatments: First, a second cold rolling process followed by a cooling aging process (deformation temperature: room temperature, deformation amount: 50%, deformation method: unidirectional synchronous rolling, deformation per pass: 15%, cooling aging temperature range: 500→350℃, cooling rate: 1.2℃ / min, cooling aging to the minimum temperature followed by direct air cooling); second, a third cold rolling process (deformation temperature: room temperature, deformation amount: 45%, deformation per pass: 10%, deformation method: unidirectional synchronous rolling); third, isothermal aging (isothermal temperature: 410℃, heating rate: 150℃ / min, time: 2h, followed by direct air cooling). Finally, the microhardness, electrical conductivity, and tensile properties of the typical aged alloy were characterized.

[0076] Performance testing:

[0077] Dislocation density: The dislocation density in the alloy matrix was measured using XRD on an Empyrean diffractometer.

[0078] β'-Cu4Ti precipitate phase and its size: The microstructure was characterized by TEM on a JEM-F200 transmission electron microscope.

[0079] Spacing between adjacent precipitate particles of various sizes: characterized by TEM structure on a JEM-F200 transmission electron microscope.

[0080] Hardness: Tested on EAM-3A-500 microhardness scale, with 10 values ​​measured each time and the average value taken.

[0081] Conductivity: Tested using a SIGMATEST 2.070 eddy current conductivity meter, with 10 values ​​measured each time and the average value taken.

[0082] Tensile strength and yield strength: measured on an AG-Xplus tensile testing machine according to international standard E8 / E8M-16a.

[0083] Elongation: Tested according to international standard GB / T 228.1-2021.

[0084] Data for all the above embodiments and comparative examples are shown in Tables 1 to 3.

[0085] Table 1. Hardness and electrical conductivity of alloys in the pre-aged state and the third cold-rolled state.

[0086]

[0087] Table 2 Tensile and electrical properties of the inventive alloy in its final state

[0088]

[0089] Table 3. Spacing and dislocation density between adjacent particles of precipitates of various sizes

[0090]

[0091]

[0092] As shown in Table 1, although pre-aging with heating can precipitate multi-scale precipitates, the distribution characteristics of these precipitates within the matrix vary with the heating rate, directly affecting the alloy's hardness and electrical conductivity. Because different multi-scale precipitates are formed within the alloy matrix, after the first cold rolling followed by heating aging, the distribution characteristics of the multi-scale precipitates and dislocation coupling within the matrix are significantly different, resulting in varying increases in hardness and electrical conductivity. If a second cold rolling deformation followed by cooling aging is performed, the alloy's hardness and electrical conductivity will inevitably differ significantly. This is similar to the hardness and electrical conductivity changes observed in the second cold-rolled alloy during the first cooling aging process, as described in Example 1. Figure 2 and 3 As shown in the figure, after the first cooling and aging process, the hardness of the alloy in the second cold-rolled state is higher than that in the initial state when the cooling and aging temperature is above 410℃, with the highest hardness occurring at 470℃. Simultaneously, due to the different particle sizes and distribution densities, differences in micro-interval hardness inevitably occur, resulting in high-hardness and low-hardness micro-regions within the alloy matrix. This manifests as a large range of measured hardness distribution; for example, the hardness range at 470℃ is 325-350 HV, corresponding to an electrical conductivity of approximately 14% IACS. However, when the temperature is continuously reduced to 350℃, the corresponding electrical conductivity can reach 20% IACS. Figure 3 As shown. Subsequently, the second cold-rolled alloy regulated in Example 3 was also subjected to the first cooling and aging process, and it was found that the corresponding changes in hardness and electrical conductivity were significantly different, such as... Figure 4 and 5As shown in the figure, during the first cooling aging process, the second cold-rolled alloy only showed comparable hardness to the initial state at 470℃ and 450℃; the hardness of other states decreased significantly. The electrical conductivity, however, steadily increased with cooling aging, reaching a maximum of 18% IACS at 350℃. In contrast, if the cooling aging of the second cold-rolled alloy in Example 5, which used a faster pre-aging rate, is further adjusted, it can be observed that the overall alloy hardness is lower than the initial state, with only a few high-hardness values ​​being comparable to or slightly higher than the initial state (e.g., ...). Figure 6 As shown in the figure. The conductivity gradually increased from 8% IACS at the initial stage to 17% IACS as the cooling and aging process progressed (e.g., ...). Figure 7 (As shown in the figure). It is evident that the heating rate used for pre-aging not only affects the hardness and electrical conductivity of the pre-aged alloy, but also significantly influences subsequent heating or cooling aging. This is mainly because the multi-scale precipitates induced by pre-aging have a significant impact on subsequent dislocation slip, pile-up, annihilation, and further precipitation of the precipitate phase.

[0093] Although the multi-scale precipitate phase and dislocation coupling distribution characteristics of the alloys in the second cold-rolled state differed after further cooling and aging in several embodiments, leading to significant differences in hardness and electrical conductivity, it is precisely because of the formation of the multi-scale precipitate phase and dislocation coupling distribution characteristics constructed in this invention that the alloy can undergo a third cold-rolling deformation. The hardness and electrical conductivity of the alloy after the third cold rolling are shown in Table 1. As can be seen from Table 1, compared with the hardness after the second cold rolling + first cooling and aging, the hardness after the third cold rolling did not increase significantly, but instead decreased to a certain extent. This may be because the dislocation density in the alloy matrix is ​​already saturated, and further increasing the amount of cold rolling deformation will only lead to intensified dislocation annihilation, thus resulting in a slight decrease. In addition to the decrease in hardness, the electrical conductivity of the alloy after cold rolling also decreased to a certain extent, as shown in Table 1. Therefore, if the alloy can be subjected to a certain period of low-temperature isothermal aging based on the multi-scale precipitate phase and dislocation coupling distribution characteristics in the third cold-rolled state, not only will the dislocation density not decrease rapidly, but more precipitate phases will also be induced, thereby better pinning dislocations and preventing their rapid annihilation. Based on isothermal aging control, further cooling aging at appropriate rates and within appropriate temperature ranges can further promote the precipitation of precipitated phases in alloy matrices with already low precipitation kinetics. Moreover, with reasonable control of the cooling aging rate, the dislocation annihilation rate can also be effectively controlled, ultimately leading to a significant improvement in the overall performance of the alloy. Just as... Figure 8The hardness changes of Examples 1, 3, and 5 after isothermal aging and slow-rate cooling aging in the third cold-rolled state, as shown in Table 2, reveal that the hardness of the alloys regulated by the three pre-aging methods decreased to varying degrees, but the electrical conductivity increased significantly, with the highest conductivity reaching over 21.6% IACS, as shown in Table 2. Although the tensile strength did not reach 1000 MPa, the tensile strength of Example 3 reached 947 MPa, and the elongation of all alloys was high, significantly higher than the elongation reported in the literature for alloys of similar strength levels. With the increase of the cooling rate used for cooling aging after isothermal aging, such as... Figure 9 As shown, the hardness of the alloys in several examples was also reduced, but the reduction was small, and the hardness distribution ranges of the different alloys also showed some differences. However, according to Table 2, the tensile strength of the alloys developed in Examples 2, 4, and 6 all reached over 1000 MPa, and their elongation and electrical conductivity were also excellent. The elongation reached 8.2%, and the electrical conductivity was around 20% IACS. The electrical conductivity of the alloy controlled in Example 2 reached as high as 20.6% IACS, all of which showed very excellent comprehensive performance.

[0094] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0095] The modified Cu-Ti alloy in this application optimizes the distribution of multi-scale precipitated phases without affecting the alloy's fundamental properties. These precipitated phases include microstructures with sizes ranging from 3 to 11 nm and 12 to 22 nm, respectively. They work together on the alloy matrix, resulting in significantly improved strength, plasticity, and electrical conductivity in the modified Cu-Ti alloy. This is because the multi-scale precipitated phases not only increase the alloy's ability to coordinate deformation and allow for controlled deformation through multiple heat treatments, but also further induce the precipitation of more multi-scale precipitated phases. Furthermore, when the multi-scale precipitated phases and dislocations exhibit suitable coupling distribution characteristics, they can synergistically enhance the alloy's strength, electrical conductivity, and plasticity.

[0096] The above are merely embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A modified Cu-Ti alloy, characterized in that, The modified Cu-Ti alloy comprises, by mass percentage: 3.0~3.5wt% Ti, ≤0.02wt% B, ≤0.02wt% Zr, with the balance being Cu. The modified Cu-Ti alloy includes a β'-Cu4Ti precipitate phase with a size of 3~11 nm and a β'-Cu4Ti precipitate phase with a size of 12~22 nm; The preparation method of the modified Cu-Ti alloy includes the following steps performed in sequence: batching, casting, homogenization heat treatment, hot rolling deformation, cold rolling deformation, solution quenching treatment, pre-aging treatment, first cold rolling, aging with heating, second cold rolling, first cooling aging, third cold rolling, isothermal aging, and second cooling aging.

2. The modified Cu-Ti alloy according to claim 1, characterized in that, The dislocation density of the modified Cu-Ti alloy is (5~7)×10⁻⁶. 14 ·m -2 .

3. The modified Cu-Ti alloy according to claim 1 or 2, characterized in that, The spacing between adjacent particles of the α'-Cu4Ti precipitate phase with a size of 3-11 nm is 6-9 nm; and / or the spacing between adjacent particles of the α'-Cu4Ti precipitate phase with a size of 12-22 nm is 10-16 nm.

4. A method for preparing the modified Cu-Ti alloy according to any one of claims 1 to 3, characterized in that, The preparation method includes the following steps performed in sequence: batching, casting, homogenization heat treatment, hot rolling deformation, cold rolling deformation, solution quenching treatment, pre-aging treatment, first cold rolling, aging with heating, second cold rolling, first cooling aging, third cold rolling, isothermal aging, and second cooling aging.

5. The preparation method according to claim 4, characterized in that, The temperature of the pre-aging treatment is 300~450℃, the heating rate of the pre-aging treatment stage is 150~300℃ / h, and the temperature is air-cooled to 25~30℃ after the pre-aging treatment is completed.

6. The preparation method according to claim 4, characterized in that, The temperature of the first cold rolling is 25~30℃, the total deformation is 40~60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5~20%; and / or the temperature of the heating and aging process is increased from 350℃ to 500℃, the heating rate is 0.5~4.6℃ / min, and water quenching is performed when the temperature of the heating and aging process is 500℃.

7. The preparation method according to claim 4, characterized in that, The second cold rolling temperature is 25~30℃, the total deformation is 40~60%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5~20%; and / or the temperature of the first cooling aging is reduced from 500℃ to 350℃, the cooling rate is 1.0~1.4℃ / min, and air cooling is performed when the temperature of the first cooling aging is 350℃.

8. The preparation method according to claim 4, characterized in that, The temperature of the third cold rolling is 25~30℃, the total deformation is 35~55%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 5~15%.

9. The preparation method according to claim 4, characterized in that, The isothermal aging temperature is 400~420℃, and the heating rate is greater than 100℃ / min during the process of heating to the isothermal aging temperature. After the isothermal aging is performed for 1~7 hours, the temperature is increased to the highest temperature of the second cooling aging at a rate greater than 100℃ / min. The second cooling aging is performed by reducing the temperature from 500℃ to 400℃ at a cooling rate of 1.0~1.4℃ / min. When the temperature of the second cooling aging is 400℃, air cooling is performed.

10. The preparation method according to claim 4, characterized in that, The homogenization heat treatment is performed at a temperature of 750~850℃ for 0.5~4h, with a heating rate of 20~80℃ / min during the process of heating to the homogenization heat treatment temperature; and / or the total deformation of the hot rolling deformation is 60~80%, the deformation method is unidirectional synchronous rolling, and the deformation per pass is 10~20%; and / or the cold rolling deformation is performed at a temperature of 25~30℃, with a total deformation of 40~55%; and / or the solution quenching treatment is performed at a temperature of 800~900℃ for 2~5h.

Citation Information

Patent Citations

  • Multi-phase synergistically strengthened copper-titanium alloy and preparation method thereof

    CN120485586A